Analisis Kritik Sosial Menggunakan Pendekatan Sosiologi Sastra Dalam Novel “Anak Semua Bangsa” Karya Pramoedya Ananta Toer Sebagai Alternatif Bahan Ajar Peserta Didik Kelas XI - Kamelia Nurul Herminati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research aims to describe the types of social criticism using the approach of literary sociology contained in the novel "Anak Semua Bangsa" by Pramoedya Ananta Toer as well as using it as an alternative teaching material for class XI students. This research uses a descriptive qualitative method. This data source uses the novel book "Anak Semua Bangsa" by Pramoedya Ananta Toer as well as sources from books or other reading materials as reference material in this research. The data that has been found in this research is a total of 17 data, namely: 1) political social criticism amounting to 2 data, 2) social economic criticism amounting to 3 data, 3) social criticism of education amounting to 2 data, 4) social criticism of culture in the novel contains only quotations of sentences related to cultural values ​​and does not contain quotations of sentences of social criticism of culture, 5) moral social criticism amounting to 5 data, 6) social criticism of family amounting to 5 data, 7) social criticism of religion in the novel only contains quotations of sentences related to religious values only and does not contain quotations of social criticism of religion, 8) social criticism of gender in the novel only contains quotations of sentences related to gender values ​​and does not contain quotations of sentences of social criticism of gender, and 9) social criticism of technology in the novel only contains quotations of sentences related to values only technology and does not contain quotations of social criticism of technology. Furthermore, the results of the analysis were adapted to the 2013 curriculum based on the Core Competencies and Basic Competencies listed in Permendikbud No. 37 of. In addition, a teaching material was created to support the learning of XI class students.